OPTIMIZATION OF REGIONAL ASSET MANAGEMENT FOR SUSTAINABLE DEVELOPMENT IN ACEH PROVINCE - Machfud, Machfud; Sulubara, Seri Mughni (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Fix assets are one element that has to be managed correctly to provide accurate financial statement information. The efficient management of regional property (fixed assets) has a significant impact on the correctness of the regional balance sheet's presentation. The objective of this research is to evaluate the Aceh Regional Financial and Asset Management Revenue Office's (DPKAD) adherence to the Minister of Home Affairs Regulation No. 19 of 2016 and the thoroughness of the source documents. It will also examine the regional property management cycle. The strategy is qualitative and makes use of descriptive analytical techniques. As an assistant manager, DPPKAD Aceh has executed 10 cycles in the management of fixed assets, according to the study results. Only 13 of the 14 necessary source papers were accessible, demonstrating that the fixed asset management at DPPKAD Aceh was not completely compliant with Regulation 19/2016. The DPPKAD Aceh should work more closely with all SKPD as the user or party in charge of developing the List of Maintenance Needs for Regional Property (DKPBMD) and the List of Maintenance Results as a means of complying with relevant laws and regulations.